2022
DOI: 10.3390/su14138155
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Design Strategy of Cosmetic Packaging in China Based on Life Cycle Assessment

Abstract: Consumptions of cosmetics present a steady growth trend from 2018 to 2021 in China. While environmental impact generated are becoming prominent issues. Numbers of research on the sustainability of cosmetics are focusing on ingredient choices and production; however, the packaging generates more impact than the ingredient extraction in some specific scenarios, and it should be paid more attention to. The role of packaging deserves deep consideration under the background of a circular economy. This research aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Design has the potential to influence purchase and consumption and can promote use behaviour, reuse and recycling. The design phase is crucial for each life cycle phase of cosmetics, as it defines the whole system (Ren et al, 2022). Different LCA conducted on cosmetics packaging show that there are different results when it comes to determining which phase has the greatest impact.…”
Section: Packaging Design In the Cosmetics Sectormentioning
confidence: 99%
See 3 more Smart Citations
“…Design has the potential to influence purchase and consumption and can promote use behaviour, reuse and recycling. The design phase is crucial for each life cycle phase of cosmetics, as it defines the whole system (Ren et al, 2022). Different LCA conducted on cosmetics packaging show that there are different results when it comes to determining which phase has the greatest impact.…”
Section: Packaging Design In the Cosmetics Sectormentioning
confidence: 99%
“…Different LCA conducted on cosmetics packaging show that there are different results when it comes to determining which phase has the greatest impact. The LCA conducted by Ren et al for glass and PET cosmetic bottles found that the end of life has the most consequential environmental impact at over 50 %, with landfilling of waste being the most severe, followed shortly by manufacturing, transport and use (Ren et al, 2022). Jaccarini & Refalo's (2017) LCA showed that in the case of a transportable cosmetic box with powder and mirror, the raw material extraction phase is the largest contributor of all life cycle phases when only life cycle energy consumption is considered.…”
Section: Packaging Design In the Cosmetics Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…Gatt and Refalo 16 evaluated the environmental impacts of reusable, recyclable and dematerialized cosmetic packages and found that the environmental impact was reduced by 74% when fully recyclable packaging materials were reused. Recently, Ren et al 17 conducted an LCA of cosmetic packaging samples made of glass, polyethylene terephthalate (PET) and high density polyethylene (HDPE) in China to determine their environmental impacts. The study's results show that the glass bottle had the greatest impact, with sanitary landfill sharing the largest impact on the life cycles of all three bottles.…”
Section: Introductionmentioning
confidence: 99%